Natural law and the law of nations in eighteenth and nineteenth-century Italy - Fiocchi Malaspina, Elisabetta; Silvestrini, Gabriella, 1961- (Brill, 2024)
"This volume sheds new light on modern theories of natural law through the lens of the fragmented political contexts of Italy in the eighteenth and nineteenth centuries, and the dramatic changes of the times. From the age of reforms, through revolution and the 'Risorgimento', the unification movement which ended with the creation of the unified Kingdom of Italy in 1861, we see a move from natural law and the law of nations to international law, whose teaching was introduced in Italian universities of the newly created Kingdom. The essays collected here show that natural law was not only the subject of a highly codified academic teaching, but also provided a broader conceptual and philosophical framework for the 'science of man'. Natural law was also a language in which reform programmes of education and politics were formulated and were acted upon."-- Provided by publisher.
Keywords: Natural law -- History -- 18th century.; Natural law -- History -- 19th century.; International law -- Italy -- History -- 18th century.; International law -- Italy -- History -- 19th century.; Droit naturel -- Histoire -- 18e siècle.; Droit naturel -- Histoire -- 19e siècle.; Droit international -- Italie -- Histoire -- 18e siècle.; Droit international -- Italie -- Histoire -- 19e siècle.; International law; Natural law; Italy; 1700-1899; History